Clinical outcome of transfemoral embolisation in patients with arteriovenous malformations of the liver in hereditary haemorrhagic telangiectasia (Weber-Rendu-Osler disease). Issue 1 (1st January 1998) - Caselitz, M; Wagner, S; Chavan, A; Gebel, M; Bleck, J S; Wu, A; Schlitt, H J; Galanski, M; Manns, M P
Abstract : Background —Arteriovenous malformations of the liver in Osler's disease may present as high output cardiac failure. A few case reports suggested that treatment with arterial embolisation may have beneficial effects in such patients. Aims —To investigate the efficacy and safety of this treatment modality in a prospective pilot study. Patients and methods —Four women and one man (aged 39–59 years) with the dominant hepatic manifestation of Osler's disease presented with symptoms of cardiac failure and elevated cardiac output. Arteriovenous malformations were treated in three to five sessions with arterial embolisation using coils. The outcome was analysed by measurement of cardiac output and scoring of clinical symptoms. Results —Embolisation was technically feasible in all patients and adequate occlusion of vascular malformations was achieved in four patients. After completion of therapy symptoms improved in four patients, while one patient suffered from abdominal pain due to cholangitis. One patient died seven months after the embolisation treatment from variceal bleeding. Mean cardiac output significantly decreased from 14.2 (range 12–17.3) l/min to 8 (range 5.9–10.6) l/min (p=0.043). After a median follow up of 23 months (range 7–50 months), three of five patients had a long lasting improvement of clinical symptoms and cardiac function. Conclusions —This first treatment series of patients with dominant hepatic involvement in Osler's disease indicates that arterial embolisation may prevent cardiac failure by significantly lowering cardiac output.